Yliopistopedagogiikka yliopistojen strategisen kehittämisen ytimessä - Lindblom, Sari (Annales Academiae Scientiarum Fennicae, 2024)
University pedagogy, in other words, research on teaching and learning at university is a relatively new discipline which is multidisciplinary by nature and draws its rich theoretical and methodological basismainly from psychology as well as from educational and social sciences. In addition, the contexts of study broaden the multidisciplinarity by collecting empirical evidence on factors contributing to high-quality learning outcomes, which is important. Research results often make intuitivesense and can even sound self-evident, but it is important to generate empirical evidence to confirm teachers’ instincts. However, empirical evidence can also reveal complicated inter-relationships or even counter-intuitive aspects, which need to be taken into account when making strategic decisions concerning the future of universities.